Evidencing the Need to Screen for Social Determinants of Health Among Boys Entering a Juvenile Prison: A Latent Profile Analysis - Fix, Rebecca L. (Youth violence and juvenile justice, 2022)
Social determinants of health influence who ends up in the juvenile legal system and how individuals fare when entering and leaving the system. The present study utilized latent profile analysis to determine the extent to which social determinants of health were present in a sample of incarcerated youth and the patterns in which they appear. The authors then examined their relationships to racial groups, depression, substance misuse, and recidivism risk. Data were from 1288 adolescent boys sentenced to a juvenile prison in one Southeastern state for serious offending (i.e., repeat offenses, offenses involving physical or sexual violence). We ran a latent class analysis to test for patterns with which youth present with various social determinants of health. Profiles with more violence exposure and higher social support were comprised of more Black boys than the referent profile. Property and sexual offenses also differed significantly from the referent profile. Altogether, results from our examination of selected social determinants of health indicated such factors meaningfully contribute to our understanding of experiences of young people in the juvenile legal system and may be targets for mental health and substance use intervention as they may contribute to problem behaviors or negative outcomes.